Antiquated ejection fraction: Basic research applications for speckle tracking echocardiography - Sturgill, Sarah L.; Shettigar, Vikram; Ziolo, Mark T. (Frontiers in Physiology, 2022)
For years, ejection fraction has been the go-to measurement for assessing the cardiovascular function of animal models in research labs. Despite technological advances, it remains the top choice among research labs for reporting heart function to this day, and is often overstated in applications and unfortunately may lead to misinterpretation of data. Clinical approaches have now surpassed research methods, allowing for deeper analysis of the tiers of cardiovascular performance (cardiovascular performance, heart performance, systolic and diastolic function, and contractility). Analysis of each tier is crucial for understanding heart performance, mechanism of action, and disease diagnosis, classification, and progression. This review will elucidate the differences between the tiers of cardiovascular function and discuss the benefits of measuring each tier via speckle tracking echocardiography for basic scientists.